The Effect of Work Environment, Motivation and Communication on Employee Performance at PT Hemada Wira Dharma - Deana Sushethio; Pujiarti Pujiarti (eCo-Buss, 2023)
The purpose of this research is to identify the extent to which PT Hemada Wira Dharma's work environment, employee motivation, and interdepartmental communication all contribute to the productivity of the company's workforce. Fifty individuals made up the sample size for this investigation. Distributed questionnaires were used for data collection, while SPSS 23 was used for data administration. The method used is descriptive method, where this method describes systematically, factually, and accurately regarding the factors studied. A statistical model was used to analyze the data; this model included the Frequency Test, Descriptive Test, Validity Test, Reliability Test, Determination Test (R2), T Test, and F Test. According to some of the data collected, the work environment variable (X1) did not have a positive and significant influence (tcount ttable -0.141 1,677), the motivating variable (X2) did (tcount > ttable 2.433 > 1,677), and the communication variable (X3) does (tcount > ttable 3.587 > 1,677). Conclusively, the independent variables work environment, motivation, and communication impact employee performance because fcount > ftable 34.425 > 2,57